2011
DOI: 10.1016/j.fm.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of fermenting microbiota in tarhana produced under controlled technological conditions

Abstract: a b s t r a c tThe purpose of this study was to evaluate the evolution of lactic acid bacteria (LAB) and yeasts during the fermentation of tarhana produced with some pasteurised ingredients and carried out at 30 and 40 C. The chemical parameters were those typical for tarhana production. Coliform bacteria were not detected during fermentation, while LAB and yeasts were in the range 10 7 e108 colony forming units (CFU) g À1. Plate counts showed an optimal development of both fermenting microbial groups and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 46 publications
2
55
0
3
Order By: Relevance
“…Acidity and pH change in this study were in agreement with the observations of previous works (Ekinci, 2005;Erbaş et al, 2006;Obanoglu et al, 1995;Settanni et al, 2011).…”
Section: Physicochemical Properties Of Tarhana Samplessupporting
confidence: 93%
See 1 more Smart Citation
“…Acidity and pH change in this study were in agreement with the observations of previous works (Ekinci, 2005;Erbaş et al, 2006;Obanoglu et al, 1995;Settanni et al, 2011).…”
Section: Physicochemical Properties Of Tarhana Samplessupporting
confidence: 93%
“…The final rod LAB of dough C and B were similar and higher than in standard tarhana (A). Erbaş et al (2005), Settanni et al (2011) andObanoglu et al (1999b) reported that LAB counts increased in the first days of fermentation and then decreased. They did never detected coliforms during the whole process.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…cremoris, Leu. mesenteroides subsp. mesenteroides, S. thermophilus, P. pentosaceus and P. acidilactici (Daglioglu, 2000;Erten and Tanguler, 2010;Settanni et al, 2011), and yeast (Rhodotorula glutinis) have also isolated in tarhana fermentation. The most important microbial group for tarhana fermentation is LAB, they have a key role in generation of the aromatic compounds, and moreover they strongly have contributed to the stability of the product during storage by the inhibition of several unwanted microorganisms.…”
Section: Tarhanamentioning
confidence: 99%
“…The most important microbial group for tarhana fermentation is LAB, they have a key role in generation of the aromatic compounds, and moreover they strongly have contributed to the stability of the product during storage by the inhibition of several unwanted microorganisms. Meanwhile, yeasts have further effects on the aromatic profile of tarhana (Settanni et al, 2011). At the end of the fermentation, dough has an acidic and sour taste and is called 'wet tarhana'.…”
Section: Tarhanamentioning
confidence: 99%
See 1 more Smart Citation